Kinetic characteristics of the luminescence decay for industrial yttrium-gadolinium-aluminium garnet based phosphors; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Lisitsyn V. M. Viktor Mikhailovich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich; Vishnyakova E. A.; Abdullin H. A.; Marhabaeva A. A.; Tulegenova A. T. (2016, 2016)
Title screen